Opicapone for the treatment of Parkinson's disease: A review of a new licensed medicine. Issue 10 (27th September 2018) - Fabbri, Margherita; Ferreira, Joaquim J.; Lees, Andrew; Stocchi, Fabrizio; Poewe, Werner; Tolosa, Eduardo; Rascol, Olivier
Abstract: Catechol‐O‐methyl transferase inhibitors are currently used as first‐line add‐on therapy to levodopa for the treatment of end‐of‐dose motor fluctuations in Parkinson's disease patients, as they increase levodopa bioavailability. Several factors hamper the use of current available catechol‐O‐methyl transferase inhibitors, that is, the moderate efficacy and multiple dosing for entacapone and the risk of liver toxicity with tolcapone. Opicapone, a new long‐acting, peripherally selective, once‐daily catechol‐O‐methyl transferase inhibitor, was recently licensed in Europe. Two phase 3 double‐blind clinical trials demonstrated opicapone efficacy in reducing OFF time by an average of about 60 minutes daily compared with placebo, without increasing ON time with troublesome dyskinesias. These effects were also maintained during a subsequent open‐label extension consisting of 1‐year follow‐up. Opicapone showed a good safety profile. From June 2016, Opicapone received the approval for marketing authorization from the European Commission as adjunctive therapy to levodopa/DOPA decarboxylase inhibitors in patients with PD and end‐of‐dose motor fluctuations. We aimed to review the clinical pharmacological data of opicapone, summarize its clinical efficacy and safety issues, and discuss its potential role in the management of Parkinson's disease. © 2018 International Parkinson and Movement Disorder Society